The relationship between bank concentration and the interest rate pass through in selected African countries - Mangwengwende, Tadiwanashe Mukudzeyi (Rhodes University, Faculty of Commerce, Department of Economics, 2010)
Given the importance of monetary policy in the operation of a successful modern economy and the use of official interest rates as tools in its implementation, this study investigates the implications of changing bank concentration on the operation of the Interest Rate Pass Through (IRPT) of official rates to bank lending and deposit rates. This is an issue made more poignant by growing mergers, acquisitions and bank consolidation exercises around the world that have brought interest to their implications for economic performance. However, with contention high in the industrial organisation theory on the likely relationship between bank concentration and the IRPT, and the outcomes of empirical investigations producing conflicting evidence, the desire to investigate the issue in the African context necessitated a thorough empirical investigation of four African countries (South Africa, Botswana, Nigeria and Zambia). This study not only extended the investigation of the issue to the African context, but it merged different IRPT measurement techniques that had not been jointly applied to this particular issue, namely; Symmetric and Asymmetric Error Correction Models, Mean Adjustment Lags, Ordinary Least Squares estimations and Autoregressive Distributed Lag models. These measures of the IRPT were compared with three firm concentration ratios on two different levels of analysis, one, over the entire period and, another, through eight year rolling windows. The results reveal that bank concentration can sometimes be related to the speed and magnitude of the IRPT but that these relationships are not consistent amongst the countries, over the entire sample period or across the two levels of analysis, suggesting reasons why empirical results have arrived at contrasting conclusions. The results revealed more evidence of a relationship between bank concentration and the magnitude of the IRPT than between bank concentration and the speed of the IRPT. Furthermore, where relationships were identified there was evidence supporting both the structure conduct performance hypothesis and the competing efficient market hypothesis as the true representation of the relationship between bank concentration and the IRPT. The key implication of the result for African countries is that increased bank concentration through bank consolidation programmes should not be automatically regarded as detrimental to the effective implementation of monetary policy through the IRPT. Consequently,banking sector regulation need not stifle bank consolidation and growth to preserve monetary policy effectiveness. Rather, since the relationship cannot be neatly represented by a single theory or hypothesis each country must determine its own interaction between bank concentration and its IRPT before policies regarding the banking sector concentration and effective monetary policy, through the use of official interest rates, are determined.
Keywords: Interest rates -- Effect of inflation on -- Africa; Monetary policy -- Africa; Prime rate; Prime rate -- Africa